2018
DOI: 10.1097/qad.0000000000002016
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of a community-based intervention on HIV and nutritional outcomes at 6 months among women living with HIV/AIDS in rural India

Abstract: Objective: To assess the impact of nurse-led Asha (Accredited Social Health Activist)-support behavioral and nutritional intervention among women living with HIV/AIDS (WLH/A) in rural India. Design: Cluster randomized-controlled trial. Methods: Sixteen Primary Health Centers serving WLH/A in Andhra Pradesh were grouped into four regional clusters that were randomly allocated into one of four arms. All four groups included Asha-support and consisted of: Asha-support only (control group); nutrition education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(48 citation statements)
references
References 34 publications
(42 reference statements)
2
46
0
Order By: Relevance
“…Sanctions against Iran have put economic pressure on the people, espe cially HIV patients, and have weakened the effectiveness of the IMB model, but in Ameri et al the IMB model was effective in adherence to the diet [22]. Similarly to our study, Nyamathi in India reported that food intake was challenging in HIV/AIDS patients, so that lack of resources, stigma, dis crimination, and poor behavior of food industry employees reduced food intake in patients [29].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Sanctions against Iran have put economic pressure on the people, espe cially HIV patients, and have weakened the effectiveness of the IMB model, but in Ameri et al the IMB model was effective in adherence to the diet [22]. Similarly to our study, Nyamathi in India reported that food intake was challenging in HIV/AIDS patients, so that lack of resources, stigma, dis crimination, and poor behavior of food industry employees reduced food intake in patients [29].…”
Section: Discussionsupporting
confidence: 69%
“…In our study, sugar consumption was reduced in the in tervention group. In the same vein, Nyamathi et al [29] found that the intervention group followed a healthy diet after the intervention and decreased consumption of un healthy foods. In the present study, an educational training method was administered and the participants were provid ed with information about healthy food.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…23,24 The lower prevalence of ASCUS and LSIL observed in our population may be because our participants had completed six months of ART adherence and nutritional intervention at the time of cytology screening, resulting in significant improvement in CD4+ T cell counts. 17,28 Previous studies have shown a strong association between CD4+ T cell recovery and regression of ASCUS and LSIL. 29,30 While studies have shown that ART is also associated with reduced HSIL and SCC, 31,32 these outcomes develop over a longer period of time, and thus longer follow-up of patients may be needed to observe reductions in HSIL and SCC.…”
Section: Discussionmentioning
confidence: 99%
“…This cross-sectional secondary analysis used data from a quasi-experimental trial funded by the National Institute of Mental Health (R01MH098728) that investigated the impact of a nurse-led ASHA (Accredited Social Health Activist)-supported behavioral and nutritional intervention among WLWH in rural Nellore and Prakasam, India between April 2014 and November 2016 [41,42]. Flyerbased recruitment was utilized to engage participants from 16 community health centers and primary health clinics.…”
Section: Design and Samplementioning
confidence: 99%